Strategi Komunikasi Bisnis PT. Maju Anugerah Solusindo dalam Menjalin Kerja Sama dengan Vendor di Industri Aplikasi Digital - Nia Ramadani; Fifit Fitriansyah; Ria Yunita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The rapid development of the digital application industry requires every company to have an effective business communication strategy, especially in collaborating with vendors as strategic external partners. The background of this research is based on the importance of business communication that not only focuses on internal information exchange, but also building harmonious, sustainable and mutually beneficial external relationships. PT Maju Anugerah Solusindo as a software development company realises that the success of cooperation with vendors greatly affects Maju Anugerah Solusindo in building and maintaining cooperation with vendors in the midst of the highly competitive digital application industry. Descriptive qualitative research method was used with data collection through in- depth interviews with management and vendors, direct observation, and case study documentation. With the aim to analyse and describe the business communication strategy used by PT Maju Anugerah Solusindo. The results showed that PT. Maju Anugerah Solusindo The supporters of the success of this strategy include management commitment, the use of appropriate communication technology, and a collaborative organisational culture. the needs of vendors are constantly changing. Overall, the business communication strategy has contributed significantly to the creation of a productive and sustainable working relationship between PT Maju Anugerah Solusindo and its vendors in the digital app industry. PT Maju Anugerah Solusindo and its vendors in the digital application industry.